Judgments of Time in Traffic Related Decision-Making Situation - Nordfang, Maria (Proceedings from the Annual Transport Conference at Aalborg University, 2007)
Judgments of time can have a crucial role for the choices drivers take while in traffic. At the same time drivers’ value of time is often predicted as being the core benefit from new road development schemes (Mackie, Jara-Días, Fowkes, 2001; Beesley, 1965). This paper uses the theoretical perspective of Kahneman & Tversky’s (1979) Prospect Theory to investigate how time is judged in traffic situations. In particular, it is examined how the framing of time- prospects, influence the drivers’ judgments. To investigate this a questionnaire was distributed on the internet. 213 participants were presented with 6 different situations related to time in traffic and asked to choose between two different time-prospects in each of the 6 situations. The 6 different choice situations were each framed in both a positive and a negative formulation. The individual participant was presented with only one of the two formulations in each choice situation. The results from the experiment indicate that the framing of the specific choice situation play a role in drivers’ judgments of time in traffic related situations, as Prospect Theory predicts. Also, the results show that special consideration must be given to judgments of time as compared to choices involving judgments of objects or money, as the perception of time differs from the perception of objects or money.